2019
DOI: 10.1177/0886260519888517
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Structural Equation Modeling Analysis and Validity of the Family Needs Screener

Abstract: Assessment that accurately categorizes families’ risk for family violence (i.e., intimate partner violence and child maltreatment) and identifies areas of family need is essential for prevention program planning, practice, and resource allocation. The Family Needs Screener (FNS) assesses risk for intimate partner violence and child maltreatment. It is used as a tool to prioritize those who are in the greatest need of services as well as plan prevention efforts in selected prevention services offered to militar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Other studies with military families have found similar family risk factors for child maltreatment. For example, relationship issues with a partner and intimate partner violence predict child maltreatment in Army families (Kaye et al, 2019). For mothers in military families, child maltreatment risk factors included family conflict, low family cohesion, and marital adjustment (Schaeffer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies with military families have found similar family risk factors for child maltreatment. For example, relationship issues with a partner and intimate partner violence predict child maltreatment in Army families (Kaye et al, 2019). For mothers in military families, child maltreatment risk factors included family conflict, low family cohesion, and marital adjustment (Schaeffer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, military families who live in geographically isolated areas (where many military installations are located) and those who live in private housing (as opposed to on installations) are more likely to report feeling socially isolated and disconnected (National Academies of Sciences, Engineering, and Medicine, 2019; U.S. Department of Defense, 2017b; Willerton et al, 2011). This is problematic as feelings of isolation predict child maltreatment in Army families (Kaye et al, 2019).…”
Section: Risk and Preventive Factors Associated With Child Maltreatme...mentioning
confidence: 99%
See 3 more Smart Citations